2021
DOI: 10.3389/fonc.2021.667174
|View full text |Cite
|
Sign up to set email alerts
|

Tongue Cancer Cell-Derived CCL20 Induced by Interaction With Macrophages Promotes CD163 Expression on Macrophages

Abstract: BackgroundCD163-positive macrophages contribute to the aggressiveness of oral squamous cell carcinoma. We showed in a previous report that CD163-positive macrophages infiltrated not only to the cancer nest but also to its surrounding epithelium, depending on the presence of stromal invasion in tongue carcinogenesis. However, the role of intraepithelial macrophages in tongue carcinogenesis remains unclear. In this study, we assessed the biological behavior of intraepithelial macrophages on their interaction wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 76 publications
0
2
0
Order By: Relevance
“…Members of this family contain a great many proteins, which perform various biological functions by binding to their receptors [ 17 ]. CCL20 and its receptor CCR6 are involved in the progression, migration, invasion and angiogenesis of cancer cells [ 18 20 ], including HCC cells [ 21 ]. In colorectal cancer, CCR6 enhances tumour angiogenesis via the AKT/NF-κB/VEGF cell signalling.…”
Section: Introductionmentioning
confidence: 99%
“…Members of this family contain a great many proteins, which perform various biological functions by binding to their receptors [ 17 ]. CCL20 and its receptor CCR6 are involved in the progression, migration, invasion and angiogenesis of cancer cells [ 18 20 ], including HCC cells [ 21 ]. In colorectal cancer, CCR6 enhances tumour angiogenesis via the AKT/NF-κB/VEGF cell signalling.…”
Section: Introductionmentioning
confidence: 99%
“…CCL20 is a small protein that is proven to be associated with colorectal and hepatocellular carcinoma [26][27][28]. Abiko et al in 2003 [29], suggested that CCL20 was shown to initiate and promote carcinogenesis in OSCC by controlling the immune response to bacteria such as Actinobacillus actinomycetemcomitans [29], as well as increasing the expression of CD163 on macrophages [30]. Very recently, Fusobacterium nucleatum was found to be positively associated with salivary CCL20 levels [31].…”
Section: Introductionmentioning
confidence: 99%